Analisa Kemampuan Lisan Mahasiswa Bahasa Inggris Universitas Muhammadiyah Aceh di Kelas Speaking Menggunakan Rubrik Penilaian - Cut Mawar Helmanda; Rahmatun Nisa (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
The main purpose of this research is to observe and analize the students’ speaking ability ini speaking class by using scoring rubric. This research was field research which observed the English Department students of Muhammadiyah Aceh University in delivering idea based on what the lecturer asked. The observation sheet was used to get data about the students’ speaking ability based on scoring rubric and the questionnaire sheet shared to get information about their problems and how they solve them. 15 students of IV semester of speaking class taken as the sample. They were taken through random sampling. From the result, there was only one student who got perfect score, and the rest were categorized as good score, average and poor. The problems that the students faced in speaking class were less confidence, anxiety, lack of vocabulary and problems in grammar ability. For those reasons, they tried to motivate themselves to be better, got enough practice, and memorized English vocabulary.